2016
DOI: 10.1128/aem.01412-16
|View full text |Cite
|
Sign up to set email alerts
|

Natural Competence of Xylella fastidiosa Occurs at a High Frequency Inside Microfluidic Chambers Mimicking the Bacterium's Natural Habitats

Abstract: Xylella fastidiosa is a xylem-limited bacterium that is the causal agent of emerging diseases in a number of economically important crops. Genetic diversity studies have demonstrated homologous recombination occurring among X. fastidiosa strains, which has been proposed to contribute to host plant shifts. Moreover, experimental evidence confirmed that X. fastidiosa is naturally competent for recombination in vitro. Here, as an approximation of natural habitats (plant xylem vessels and insect mouthparts), recom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
39
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 18 publications
(43 citation statements)
references
References 63 publications
(81 reference statements)
4
39
0
Order By: Relevance
“…This suggested that the insertion at pilQ rendered BBI64 noncompetent and nonmotile. Another strain (pglA _ -KmR) that lacked twitching and competence in a previous study (Kandel et al 2016) showed an insertion in the pilM (PD1695) coding region, which was also confirmed by further sequencing (data not shown). No frame-shift mutation was observed in the competence-related genes in another noncompetent and nonmotile strain, Georgia Plum (data not shown).…”
Section: Resultsmentioning
confidence: 50%
See 4 more Smart Citations
“…This suggested that the insertion at pilQ rendered BBI64 noncompetent and nonmotile. Another strain (pglA _ -KmR) that lacked twitching and competence in a previous study (Kandel et al 2016) showed an insertion in the pilM (PD1695) coding region, which was also confirmed by further sequencing (data not shown). No frame-shift mutation was observed in the competence-related genes in another noncompetent and nonmotile strain, Georgia Plum (data not shown).…”
Section: Resultsmentioning
confidence: 50%
“…Strain WM1-1 had the highest recombination frequency and showed highest motility among strains, while the two noncompetent strains were nonmotile. Positive correlation between recombination frequency and twitching motility was also suggested in our previous study using different media components (Kandel et al 2016). Since components of type IV pili are involved in both natural competence and twitching motility in several naturally competent gram-negative bacteria (Seitz and Blokesch 2013a), including X. fastidiosa (Kung and Almeida 2014), the activity of type IV pili could govern both of these phenomena.…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations